The Theoretical Description for the Perylaldehyde Aldoxime Electrochemical Determination, Assisted by the Novel Squaraine Dye – VO(OH) - Composite - Tkach, Volodymyr V.; Kushnir, Marta V.; Ahafonova, Oleksandra V.; Biryuk, Igor G.; de Oliveira, Silvio Cesar; Yagodynets´Petro I.; Kormosh, Zholt O.; dos Reis , Lucinda Vaz; Palamarek, Karina V.; Nezveshchuk-Kohut, Tetyana S. (Orbital: The Electronic Journal of Chemistry, 2020)
For the first time, the perillaldehyde aldoxime electrochemical determination has been evaluated from the theoretical point of view. The correspondent mathematical model, including different scenarios of the electroanalytical process, has been developed and analyzed by means of linear stability theory and bifurcation analysis. The model analysis clearly shows that the composite of a squaraine dye in organic phase and vanadium oxyhydroxide in the inorganic phase may be an efficient electrode modifier for perillaldehyde aldoxime electrochemical determination. On the other hand, both oscillatory and monotonic instabilities may be realized in the electroanalytical process, and their probability will strongly depend on the direction of the electroanalytical scenario in the concrete conditions. DOI: http://dx.doi.org/10.17807/orbital.v12i3.1498